Aspectos éticos de las tecnologías de la información y de la comunicación: La ética de la computación, internet y la world wide web - Luisa Montuschi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2005)
– Information and communication technologies are invading all aspects of human existence and are challenging many individual and social values. Computer technologies, Internet and the World Wide Web have created possibilities at global level for individuals and organizations that were not available before. But many ethical questions have arisen because changes are affecting human relationships, social institutions and basic moral notions. This paper considers some ethical issues related to the information and communication technologies, particularly the questions associated with computer technology, the Internet and the World Wide Web.
Keywords: 330; Informationstechnik; Internet; Ethik; Verantwortung